Spontaneous rupture of the spleen at full term during pregnancy: a case report - Heng Xu; Jia-Ping Lu (Journal of International Medical Research, 2023)
Spontaneous rupture of the spleen during pregnancy is a rare, fatal disease. This condition is easily misdiagnosed as uterine rupture, placental abruption, or other obstetric diseases; and if a timely diagnosis is not made and effective treatment instituted, serious sequelae rapidly develop, including hemorrhagic shock and maternal and fetal death. Here, we report a case of spontaneous splenic rupture in a woman in her third trimester of pregnancy. Furthermore, through a literature review, we discuss the possible presentations, symptoms, and causes of splenic rupture during pregnancy, in the hope of facilitating the early diagnosis and treatment of this condition.